2005
DOI: 10.1073/pnas.0502165102
|View full text |Cite
|
Sign up to set email alerts
|

Structure and ESCRT-III protein interactions of the MIT domain of human VPS4A

Abstract: The VPS4 AAA ATPases function both in endosomal vesicle formation and in the budding of many enveloped RNA viruses, including HIV-1. VPS4 proteins act by binding and catalyzing release of the membrane-associated ESCRT-III protein lattice, thereby allowing multiple rounds of protein sorting and vesicle formation. Here, we report the solution structure of the N-terminal VPS4A microtubule interacting and transport (MIT) domain and demonstrate that the VPS4A MIT domain binds the C-terminal half of the ESCRT-III pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
175
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(185 citation statements)
references
References 43 publications
10
175
0
Order By: Relevance
“…Similarly, the ⌬RS but not the ⌬S truncation largely eliminated the interaction of GST-CHMP3 151-end with Vps4A (Fig. 5B), shown previously to bind to the C-terminal domains of CHMP proteins (41). In contrast, neither mutation affected binding to the N-terminal CHMP3 1-150 FLAG fragment (Fig.…”
Section: Accessibility Of the Binding Site For The Acidic Domain Corrmentioning
confidence: 83%
“…Similarly, the ⌬RS but not the ⌬S truncation largely eliminated the interaction of GST-CHMP3 151-end with Vps4A (Fig. 5B), shown previously to bind to the C-terminal domains of CHMP proteins (41). In contrast, neither mutation affected binding to the N-terminal CHMP3 1-150 FLAG fragment (Fig.…”
Section: Accessibility Of the Binding Site For The Acidic Domain Corrmentioning
confidence: 83%
“…Five Ala and/or Gly residues (9,16,28,35) are highly conserved and are involved in the formation of an 'Alanine zipper' between the first two helixes (see Supplementary material Figure S4) [64]. The 'Alanine zipper' also participates in the coiled coil formation as a result of its interaction with aromatic and/or large hydrophobic side-chain residues as Leu, Tyr and Ile.…”
Section: Vps4mentioning
confidence: 99%
“…VPS4 proteins act by binding, catalyzing and energizing the dissociation of the ESCRT-III complex and the release of the membrane-associated SNF7 domain proteins into the cytoplasm for further rounds of sorting [57,63]. In diverse protein-protein interaction studies, it has been shown that VPS4 and its two mammalian homologs VPS4B or SKD1 and VPS4A or SKD2 interact with 'classical' ESCRT-III complex components (SNF7 or CHMP4, VPS2 or CHMP2, VPS20 or CHMP6) and the associated proteins VPS46 or CHMP1, and VTA1 or SBP1 [20][21][22]24,25,[63][64][65][66].The two highly related human VPS4 proteins are 80% identical and share approximately 60% amino acid identity with the yeast VPS4 protein (see Supplementary material Table S5 and Figure S4). Apart from the catalytic AAA-ATPase domain of VPS4 proteins, their substrate specificity is defined by a 70-amino acid N-terminal MIT domain (see Figure S4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A mammalian orthologue of Vps46p, CHMP1B, interacts by yeast two-hybrid analysis with spastin, another mammalian AAA-type ATPase that when mutated is the most common cause of hereditary spastic paraplegia (26). Recently, the microtubule interacting and transport (MIT) domain of VPS4A, the other mammalian Vps4p orthologue, was solved and found to bind CHMP1B in vitro (27).…”
mentioning
confidence: 99%